2020
DOI: 10.1371/journal.pmed.1003017
|View full text |Cite
|
Sign up to set email alerts
|

Association of puberty timing with type 2 diabetes: A systematic review and meta-analysis

Abstract: BackgroundEmerging studies have investigated the association between puberty timing, particularly age at menarche (AAM), and type 2 diabetes. However, whether this association is independent of adiposity is unclear. We aimed to systematically review published evidence on the association between puberty timing and type 2 diabetes (T2D) or impaired glucose tolerance (IGT), with and without adjustment for adiposity, and to estimate the potential contribution of puberty timing to the burden of T2D in the United Ki… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
50
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 60 publications
(199 reference statements)
0
50
0
5
Order By: Relevance
“…Global secular trends towards earlier timing of puberty [1,2] represent an increasingly important public health issue. Substantial evidence has demonstrated that an earlier timing of puberty is associated with poorer mental and physical health in later life [3][4][5][6][7]. While the underlying mechanisms remain unclear, greater childhood growth and obesity have been associated with both earlier puberty [8] and adverse health outcomes [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Global secular trends towards earlier timing of puberty [1,2] represent an increasingly important public health issue. Substantial evidence has demonstrated that an earlier timing of puberty is associated with poorer mental and physical health in later life [3][4][5][6][7]. While the underlying mechanisms remain unclear, greater childhood growth and obesity have been associated with both earlier puberty [8] and adverse health outcomes [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…These findings have become a matter of intense debate and concern due to the association of earlier ages at puberty with increased prevalence of childhood obesity and adverse consequences in adult life ( Ahmed et al., 2009 ; Biro et al., 2006 ; Burt Solorzano and McCartney, 2010 ; Ong et al., 2006 ; Shalitin and Kiess, 2017 ; Walvoord, 2010 ). Premature pubertal development in girls is associated with a series of adult morbidities including breast cancer, cardiovascular diseases, type 2 diabetes, and obesity ( Berkey et al., 1999 ; Cheng et al., 2020 ; Day et al., 2015 , 2017 ; Lakshman et al., 2008 ; Petridou et al., 1996 ; Petry et al., 2018 ). The molecular mechanisms and the cross talk between metabolism and pubertal development are not fully understood, but tissue- and/or cell-specific genome-wide association studies (GTEx, GWAS projects) have identified the brain as the main site of genetic enrichment of transcripts with roles in age at menarche and/or obesity susceptibility ( Day et al., 2017 ; Locke et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The age when an adolescent girl first begins menses affects their sexual and reproductive health as well as non-reproductive health [ 4 ]. Earlier age at menarche has been associated with a higher risk of metabolic syndrome [ 5 , 6 ], type 2 diabetes [ 7 , 8 ], hormone-related cancers [ 9 , 10 ], cardiovascular disease, and mortality later in life during adulthood [ 11 ]. In Iranian women, the risk of pre-diabetes, diabetes, and metabolic syndrome was 2.3–3.6 higher in women with menarcheal age < 11 than those with menarcheal age 13–14 years [ 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Iranian women, the risk of pre-diabetes, diabetes, and metabolic syndrome was 2.3–3.6 higher in women with menarcheal age < 11 than those with menarcheal age 13–14 years [ 6 , 8 ]. It has also been estimated that the risk of type 2 diabetes is reduced by 9% per 1-year later occurrence of menarche [ 7 ], and the risk of metabolic syndrome is increased by 8% per 1-year decrease in AAM [ 5 ].…”
Section: Introductionmentioning
confidence: 99%